IMF DALAM PERSPEKTIF TEORI DEPEDENSI DAN PERUBAHAN - Khadijah, Siti (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2014)
Economic crisis that hit Indonesia in mid-1997 resulted in Indonesian debt , both government debt and private sector due to the weakening rupiah soaring . As a result of the crisis , since 1998 , the government has shaped domestic debt bonds . The debt was used to finance the dam restruktrisasi banking recapitula-tion almost bangkrut.Dalam this case , the IMF emerged a hero who will be the savior of the Indonesian economy in the form of loans . Through its lending , the IMF actually just adds to the burden of debt to support the balance of payments position . Therefore , the recovery was apparent because the IMF is not the result of an increase in private capital flows and increase net exports . The emergence of dependency theory as the impact of economic policies from the IMF have led to changes in the economy in Indonesian society , both positive and negative . This is consistent with the existence of two views of the dependency theory expressed by Sztompka (2008 ) , the outlook is pessimistic ( Andre Gunder Frank , 1969) and the outlook is rather optimistic ( F Cardoso and E. Falet , 1964) . Symptoms of social change arising from both dependency theory .